2012
DOI: 10.1128/aem.01154-12
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of Chloramphenicol and Florfenicol by a Novel Chloramphenicol Hydrolase

Abstract: ABSTRACTChloramphenicol and florfenicol are broad-spectrum antibiotics. Although the bacterial resistance mechanisms to these antibiotics have been well documented, hydrolysis of these antibiotics has not been reported in detail. This study reports the hydrolysis of these two antibiotics by a specific hydrolase that is encoded by a gene identified from a soil metagenome. Hydrolysis of chloramphenicol has been recognized in cell extracts of Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(45 citation statements)
references
References 36 publications
1
43
1
Order By: Relevance
“…These genes code for the aforementioned rRNA methylases and mediate phenicol resistance by target site modification (Kehrenberg et al, 2005: Long et al, 2006Hansen and Vester, 2015). Moreover, a single gene of unknown origin that confers chloramphenicol resistance by hydrolysis has been described (Tao et al, 2012). During whole genome sequencing, cat-like genes have been annotated in the genomes of several bacteria, e.g., Brucella melitensis (GenBank NC_003317) and Bacillus cereus (GenBank NC_004722).…”
Section: Chloramphenicol Resistancementioning
confidence: 99%
“…These genes code for the aforementioned rRNA methylases and mediate phenicol resistance by target site modification (Kehrenberg et al, 2005: Long et al, 2006Hansen and Vester, 2015). Moreover, a single gene of unknown origin that confers chloramphenicol resistance by hydrolysis has been described (Tao et al, 2012). During whole genome sequencing, cat-like genes have been annotated in the genomes of several bacteria, e.g., Brucella melitensis (GenBank NC_003317) and Bacillus cereus (GenBank NC_004722).…”
Section: Chloramphenicol Resistancementioning
confidence: 99%
“…We have also observed that after a few passages in solid and liquid media some of these strains often appear to lose their qnr determinants (A. Tomova and F. C. Cabello, unpublished). Elimination of strains with larger IZD for florfenicol may have similarly biased against strains containing only floR resistance genes and lacking other florfenicol resistance genes (Tao et al, 2012). A large proportion of the AR bacteria from the aquaculture and the non-aquaculture sites did not contain most of the tested genes (Table 1).…”
Section: Sitementioning
confidence: 99%
“…The majority of acquired antibiotic resistance genes in bacterial pathogens are obtained via horizontal gene transfer (HGT) (Ochman et al, 2000), likely with environmental origins (Benveniste and Davies, 1973; Wright, 2010; D'Costa et al, 2011). Accordingly, an increasing impetus has been placed on cataloging antibiotic resistance reservoirs (Allen et al, 2009b, 2010), determining how resistance genes are most readily transferred to the clinic (Marshall and Levy, 2011; Smillie et al, 2011), and identifying resistance mechanisms heretofore unseen in clinical settings (Jeon et al, 2011; Tao et al, 2012). …”
Section: Overviewmentioning
confidence: 99%
“…The protein changes that enable it to also hydrolyze β-lactams are currently unidentified. A novel chloramphenicol acetate esterase, EstDL136, isolated from a soil metagenome, hydrolyzes the amide linkage of both chloramphenicol and its synthetic derivative florfenicol (Tao, 2011; Tao et al, 2012). Many of the surrounding genes in the metagenomic fragment are most closely related to Sphingomonadaceae, which are frequently considered for bioremediation for their ability to degrade many compounds (Stolz, 2009).…”
Section: Novel Resistance Mechanisms Uncovered By Functional Metagenomentioning
confidence: 99%